Innovation in technology solutions for erecting large-span coatings through module lifting - Tonkacheiev, Hennadii; Ignatenko, Oleksandr; Rashkivskyi, Volodymyr; Dubovyk, Iryna; Zaiets, Yuri (Cadernos de Educação Tecnologia e Sociedade, 2024)
Based on the conducted analysis of the characteristics of known organizational and technological options for non-crane lifting, including the preliminary assembly of structural-technological coating blocks on low scaffolding using the pulling method with hydraulic lifting modules placed on the tops of design columns, or the pushing method, where the support beams are pushed to the design height resting on the tops of growing lifting column shafts with the growing unit located on the foundations, a new technology has been developed. This technology for large-span coatings erection uses mechanized process equipment in the form of lifting modules. According to this method, the vertical movement of the bearing beams of the large-span coating, pre-assembled into a structural-technological block on the foundations, is performed by pushing within the space between paired columns of the supporting frame, resting on the tops of the growing installation columns. The growing up of installation column sections occurs by alternately resting the column sections on the hydraulic jacks of the lifting modules, located in the intercolumn space on the foundations, and on the lifting latch beams fixed on the external surfaces of the paired columns. Vertical guiding profiles are fixed on the internal surfaces of the paired columns to function as deviation limiters for the column sections during the growing process. This approach reduces the amount of high-altitude assembly work to the operations of final securing of the coating beams at the design height between the tops of the paired columns of the supporting frame. It automates all processes of growing the installation column sections and moving the bearing beams of the coating from the foundation level to the column top level, reducing the overall number of construction and assembly operations, shortening the erection timelines for large-span coatings, and ensuring the complete execution of erection work within a tightly built site, with dimensions not exceeding the planned dimensions of the large-span coating being erected.